2017
DOI: 10.1101/sqb.2017.82.034272
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry from Asymmetry or Asymmetry from Symmetry?

Abstract: The processes of DNA replication and mitosis allow the genetic information of a cell to be copied and transferred reliably to its daughter cells. However, if DNA replication and cell division were always carried out in a symmetric manner, it would result in a cluster of tumor cells instead of a multicellular organism. Therefore, gaining a complete understanding of any complex living organism depends on learning how cells become different while faithfully maintaining the same genetic material. It is well recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 138 publications
2
21
0
Order By: Relevance
“…Meanwhile, the previously identified asymmetric H3 (Tran et al, 2012), the differential phosphorylation at Thr3 of H3 (Xie et al, 2015), and the herein reported asymmetric sister centromeres act as a series of cis-factors. Together, temporally asymmetric microtubules coordinate with asymmetric sister centromeres to ensure differential sister chromatid attachment followed by segregation to generate two epigenetically distinct daughter cells, a phenomenon that is consistent with what has been previously hypothesized (Kahney et al, 2017;Malik, 2009;Yamashita, 2013). We propose that this series of interactions represent a 'mitotic drive' phenomenon during the asymmetric division of Drosophila male GSCs ( Figure 5I).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Meanwhile, the previously identified asymmetric H3 (Tran et al, 2012), the differential phosphorylation at Thr3 of H3 (Xie et al, 2015), and the herein reported asymmetric sister centromeres act as a series of cis-factors. Together, temporally asymmetric microtubules coordinate with asymmetric sister centromeres to ensure differential sister chromatid attachment followed by segregation to generate two epigenetically distinct daughter cells, a phenomenon that is consistent with what has been previously hypothesized (Kahney et al, 2017;Malik, 2009;Yamashita, 2013). We propose that this series of interactions represent a 'mitotic drive' phenomenon during the asymmetric division of Drosophila male GSCs ( Figure 5I).…”
Section: Discussionsupporting
confidence: 85%
“…In general, ACD gives rise to two daughter cells with distinct fates, which could occur during development, as well as tissue homeostasis and regeneration (Clevers, 2005;Kahney et al, 2017;Knoblich, 2010;Morrison and Kimble, 2006;Venkei and Yamashita, 2018). Many studies have helped our understanding how this difference in cell fate could be achieved in stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important context for understanding cell fate specification is asymmetric cell division, where the two daughter cells establish different cell fates following a single division. Many stem cells undergo asymmetric division to produce both a self-renewing stem cell and a differentiating daughter cell [1][2][3][4][5] . Here we show that histone H4 is inherited asymmetrically in asymmetrically dividing Drosophila male germline stem cells, similar to H3 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetric cell division (ACD) has been characterized in multiple systems where it plays an essential role in generating cells with distinct fates in development, homeostasis, and tissue regeneration 3,4,7,8 . Stem cells, in particular, often use ACD to give rise to one daughter cell capable of self-renewal and another daughter cell in preparation for terminal differentiation [1][2][3][4][5] . In spite of the crucial role that epigenetic mechanisms play in regulating cell fate decisions during development [9][10][11] , it remains unclear how stem cells and differentiating daughter cells establish different epigenomes following ACD.…”
Section: Main Textmentioning
confidence: 99%